Epidermal Integrin α3β1 Regulates Tumor-Derived Proteases BMP-1, Matrix Metalloprotease-9, and Matrix Metalloprotease-3 - Whitney M. Longmate; Rakshitha Pandulal Miskin; Livingston Van De Water; C. Michael DiPersio (Elsevier, 2021)
As the major cell surface receptors for the extracellular matrix, integrins regulate adhesion and migration and have been shown to drive tumor growth and progression. Previous studies showed that mice lacking integrin α3β1 in the epidermis fail to form skin tumors during two-step chemical tumorigenesis, indicating a protumorigenic role for α3β1. Furthermore, genetic ablation of α3β1 in established skin tumors caused their rapid regression, indicating an essential role in the maintenance of tumor growth. In this study, analysis of immortalized keratinocyte lines and their conditioned media support a role for α3β1 in regulating the expression of several extracellular proteases of the keratinocyte secretome, namely BMP-1, matrix metalloprotease (MMP)-9, and MMP-3. Moreover, immunofluorescence revealed reduced levels of each protease in α3β1-deficient tumors, and RNA in situ hybridization showed that their expression was correspondingly reduced in α3β1-deficient tumor cells in vivo. Bioinformatic analysis confirmed that the expression of BMP1, MMP9, and MMP3 genes correlate with the expression of ITGA3 (gene encoding the integrin α3 subunit) in human squamous cell carcinoma and that high ITGA3 and MMP3 associate with poor survival outcome in these patients. Overall, our findings identify α3β1 as a regulator of several proteases within the secretome of epidermal tumors and as a potential therapeutic target.